2012
DOI: 10.1021/cb300261e
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating JNK Signaling with (−)-Zuonin A

Abstract: Recently, in a virtual screening strategy to identify new compounds targeting the D-recruitment site (DRS) of the c-Jun N-terminal kinases (JNKs), we identified the natural product (-)-zuonin A. Here we report the asymmetric synthesis of (-)-zuonin A and its enantiomer (+)-zuonin A. A kinetic analysis for the inhibition of c-Jun phosphorylation by (-)-zuonin A revealed a mechanism of partial competitive inhibition. Its binding is proposed to weaken the interaction of c-Jun to JNK by approximately 5-fold, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The pose appears to be further stabilized by the stacking of one of its 1,3-benzodioxole rings between the groove formed by Arg127, Cys163, and Asp162 (Supplementary Figure 1A). This pose was quite similar to a (−)-zuonin A binding mode proposed by Kaoud et al[7] The highest scoring pose for (−)-zuonin A was pose 10 as shown in Table 1. This pose also interacted with the S 2 site and had a chemscore of 25.7.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The pose appears to be further stabilized by the stacking of one of its 1,3-benzodioxole rings between the groove formed by Arg127, Cys163, and Asp162 (Supplementary Figure 1A). This pose was quite similar to a (−)-zuonin A binding mode proposed by Kaoud et al[7] The highest scoring pose for (−)-zuonin A was pose 10 as shown in Table 1. This pose also interacted with the S 2 site and had a chemscore of 25.7.…”
Section: Resultssupporting
confidence: 79%
“…Lastly, it is important to address a previous (−)-zuonin A/JNK interaction study performed by Kaoud et al[7] which proposed a model of (−)-zuonin binding where the inhibitor was bound to the S 2 region of JNK. Residues that were considered important for (−)-zuonin A binding to the S 2 site were mutated to alanines and kinetic/inhibition assays were performed on the mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others suggested the differential effects of this compound on MK2 and ATF2 phosphorylation were a function of substrate:kinase stoichiometry and not due to the substrate selectivity of the compound [72]. A previous study indicated that the natural product zuonin A can target the DRS on JNK MAPK and inhibit phosphorylation of c-Jun [73]. Similarly, BI-78D3 was a small molecule identified to compete with a D-domain-containing peptide found on the JNK-interacting protein-1 (JIP1) and inhibits interactions with JNK1 [74].…”
Section: Discussionmentioning
confidence: 99%
“…[10] Recently, inhibitors targeting the D-recruitment site (DRS) of JNK and ERK have been reported. [11][12][13][14][15] Inhibitors that bind to an allosteric site in the MAPK insert region of p38a, [16,17] and a substrate-selective inhibitor that binds in regions adjacent to the ATP-binding site [18,19] have been described, but no DRS-targeting p38a inhibitors have been reported. ATP-competitive and "DFG-out"-type p38a inhibitors have been evaluated in the clinic for treatment of inflammatory diseases [20][21][22][23] and p38a may also be a target for cancer treatment.…”
mentioning
confidence: 99%